Mucocutaneous Manifestations and Associated Factors in Patients with Crohn’s Disease - Kayar, Yusuf; Dertli, Ramazan; Konür, Şevki; Ağın, Mehmet; Al Kafee, Abdullah; Baran, Bülent; Çiftçibaşı Örmeci, Aslı; Akyüz, Filiz; Demir, Kadir; Beşışık, Fatih; et al. (Turkish Journal of Gastroenterology, 2022)
Background: One-third of all extraintestinal manifestations are mucocutaneous findings in patients with Crohn’s disease and there is a relationship between some risk factors. Our aim is to evaluate factors associated with mucocutaneous manifestations in our cohort of patients with Crohn’s disease with a follow-up duration of up to 25 years. Methods: In the study, 336 patients with Crohn’s disease who were followed up between March 1986 and October 2011 were included. The demographic characteristics, Crohn’s disease-related data, and accompanying mucocutaneous manifestations were recorded. The cumulative probability of mucocutaneous extraintestinal manifestations and possible risk factors were analyzed. Results: Oral and skin involvement were detected in 109 (32%) and 31 (9.2%) patients, respectively. The cumulative probability of developing oral and skin manifestations were 43.2% and 20.3%, respectively. Cox regression analysis showed that female gender (odds ratio: 3.28, 95% CI: 1.51-7.14, P = .003) and corticosteroid use (odds ratio: 7.88, 95% CI: 1.07-57.97, P = .043) are independently associated with the development of skin manifestations, while family history (odds ratio: 3.59, 95% CI: 2.18-5.93, P < .001) and inflammatory-type disease (odds ratio: 1.776, 95% CI: 1.21-2.61, P = .004) were independently associated with the development of oral ulcers. Conclusion: Mucocutaneous extraintestinal manifestations are associated with female gender, corticosteroid use, family history, and disease type in a large cohort of patients with Crohn’s disease. Defining the specific relationships of immune-mediated diseases will help to better understand the pathogenesis of Crohn’s disease and associated mucocutaneous manifestations and to use more effective treatments. Cite this article as: Kayar Y, Dertli R, Konür S, et al. Mucocutaneous manifestations and associated factors in patients with Crohn’s disease. Turk J Gastroenterol. 2022;33(11):945-954.